Microglandular hyperplasia of the cervix: frequency in cone specimens, histological patterns, clinical aspects and immunohistochemical markers for differential diagnosis with adenocarcinoma Hiperplasia microglandular da endocérvice: freqüência em peças de conização, padrões morfológicos, aspectos clínicos e marcadores imuno-histoquímicos no diagnóstico diferencial com o adenocarcinoma - Inês Liguori Padrão; Liliana Aparecida Lucci De Angelo Andrade (Sociedade Brasileira de Patologia Clínica, 2006)
Although endocervical microglandular hyperplasia (MGH) is a common diagnosis, it can be confused with adenocarcinoma (ACa), mainly of the clear cell type. OBJECTIVES: Evaluate the frequency of MGH diagnosis in conization specimens, their histological patterns and characterize the differential diagnosis between MGH and ACa through immunohistochemical markers, as well as some clinical aspects. METHODS: We reviewed 223 cervical cones and 50 ACa in cervical biopsies in order to: 1) assess the frequency of MGH in cones; 2) verify immunohistochemical expression of p53, carcinoembryonic antigen (CEA) and Ki67 in both lesions; 3) correlate the findings to age, parity and hormonal status. RESULTS: We found 35 cases of MGH (15.7%), of the following patterns: 21 glandular (60%); 7 reticular (20%); 6 trabecular (17.1%) and one solid (2.8%). Average age was 36 years and mean parity was three children. Of the MGH patients, 51.42% were pregnant or made use of some hormonal therapy. ACa occurred in older patients (mean: 53 years), multiparous and with no hormonal history. CEA was negative in MGH and positive in 62% of ACa. Ki67 was weakly positive (5%-10% stained nuclei) in 8.6% of MGH and strong (> 40% stained nuclei) in 80% of ACa. p53 expression was negative in MGH and only present in 10% of ACa. CONCLUSIONS: MGH was common in cones, mainly in young women. Half of the cases were associated with hormonal therapy or pregnancy. CEA and Ki67 were useful but p53 expression was not important for the differential diagnosis with adenocarcinoma. Embora a hiperplasia microglandular da endocérvice (MGH) seja um diagnóstico freqüente, algumas vezes pode ser confundida com adenocarcinoma (ACa), principalmente de células claras. OBJETIVOS: Avaliar a freqüência da MGH em cones de colo uterino, seus padrões histológicos e o diagnóstico diferencial entre MGH e ACa, através de marcadores imuno-histoquímicos e de alguns aspectos clínicos. MÉTODOS: Foram revisados 223 cones, bem como 50 biópsias cervicais com o diagnóstico de adenocarcioma para: 1) verificar a freqüência de MGH nos cones; 2) avaliar a expressão de p53, antígeno carcinoembrionário (CEA) e Ki67 nas lesões; 3) correlacionar as lesões com idade, paridade e estado hormonal. RESULTADOS: MGH ocorreu em 35 cones (15,7%), com os padrões glandular (21 [60%]); reticular (7 [20%]); trabecular (6 [17,1%]) e sólido (um [2,8%]). A média de idade foi 36 anos e de paridade, três filhos; 51,42% estavam grávidas ou usavam terapia hormonal. O ACa ocorreu em pacientes mais velhas (média: 53 anos), multíparas e sem história hormonal. CEA foi negativo em todas MGH e positivo em 62% dos ACa. Ki67 apresentou reatividade baixa (5% a 10% dos núcleos corados) em 8,6% das MGH e alta (> 40% dos núcleos corados) em 80% dos ACa. p53 foi negativo na MGH e positivo em apenas 10% dos ACa. CONCLUSÃO: MGH foi freqüentemente encontrada em cones, principalmente em jovens, sendo metade dos casos associada a terapia hormonal ou gravidez. As expressões do CEA e do Ki67 foram importantes no diagnóstico de ACa, porém o p53 não contribuiu para diferenciar as lesões.